Empowering and Engaging European building users for energy efficiency. (December 2020) - Morton, A.; Reeves, A.; Bull, R.; Preston, S.
Abstract: Amidst the challenge of improving energy efficiency in the built environment, increasing attention is being put on how to engage and empower building users. Research shows that improving and widening user engagement, such as involving users in co-designing interventions, has potential to foster greater acceptance and impact. In this context, Information and Communication Technology (ICT) has a major role to play, through feedback tools, smartphone or web-based apps, interactive dashboards and gamification. However, there are few empirical accounts exploring how user engagement can effectively shape development of an ICT-based energy efficiency intervention. This paper presents findings from the eTEACHER project which aims to empower building energy end-users to reduce energy consumption through a set of related ICT-based interventions. These interventions, including a web-based app and building-specific 'what-if' analysis have been developed by drawing upon feedback from pilot users in 12 buildings, including both residential and non-domestic, across three EU countries. A structured evidence-based approach to user engagement was followed, which included site visits, a series of building user workshops and a questionnaire. The paper reflects on the challenges and benefits of empowering and engaging building users across a wide range of building types, residential, offices, schools and health care centres using a single app. Our findings show common challenges across building types in tackling existing inefficient energy behaviours. However significant hurdles were encountered in implementing the ICT-based interventions, which are building specific. Based upon this, recommendations on how engagement processes can support the development of ICT-based interventions are put forward.